Human nature and motivation: a comparative analysis between western and Islamic psychologies - Abdul Razak, Mohd Abbas; Mustapha, Maziah; Ali, Md Yousuf (IIUM, 2017)
In the fi eld of psychology, the topics on human nature and motivation have been quite extensively discussed. These two topics are interrelated and inseparable. Any endeavor to understand man and his potentials makes it necessary for one to venture into the study of human nature. Major topics in psychology like motivation, personality, creativity, psychotherapy, mental health, etc. could be well understood with a proper understanding on human nature. In the light of this reality, what makes this research an appealing and interesting one is the fact that the researchers had comparatively analyzed the ideas on human nature and motivation showcased to the world by Western and Islamic psychologies. The fact that there exist a great number of schools of thought in Western psychology, the researchers had narrowed their scope of investigation to three only. As such, they discussed the ideas on human nature and motivation as conceptualized in Psychoanalysis, Radical Behaviorism and Humanistic psychology. Upon analyzing Western theories, the researchers performed a compare and contrast analysis with ideas provided by Islamic psychology on human nature and motivation. This academic exercise was done in the hope of identifying as to whether there exist any similarity and difference between the two psychologies. Since the nature of this study was a qualitative one, the researchers conducted a library research to collect the relevant data. In analyzing the data related to the study, the researchers used the content and textual analysis methods.